Efficacy and safety of rivaroxaban vs. warfarin in patients with non-valvular atrial fibrillation and a history of cancer: observations from ROCKET AF - Chen, Sean T.; Hellkamp, Anne S.; Becker, Richard C.; Berkowitz, Scott D.; Breithardt, Günter; Fox, Keith A. A.; Hacke, Werner; Halperin, Jonathan L.; Hankey, Graeme J.; Mahaffey, Kenneth W.; Nessel, Christopher C.; Piccini, Jonathan P.; et al. (European heart journal - quality of care and clinical outcomes, 2018)
Aims: The management of anticoagulation therapy in patients with atrial fibrillation (AF) and cancer is challenging due to increased thrombotic and bleeding risks. We sought to determine the safety and efficacy of rivaroxaban in patients with AF and a history of cancer. METHODS AND RESULTS: ROCKET AF randomized 14 264 patients with AF to rivaroxaban or warfarin with a median follow-up of 1.9 years. Cox regression models were used to assess the association between cancer history and clinical outcomes, and the relative treatment effect of rivaroxaban vs. warfarin in these patients. A total of 640 patients enrolled in ROCKET AF had a history of cancer, with the most common types being prostate (28.6%), colorectal (16.1%), and breast (14.7%) cancer. Patients with a history of cancer were older, more frequently male, more likely to have prior vitamin K antagonist (VKA) use and had higher rates of overall bleeding [hazard ratio (HR) 1.30, 95% confidence interval (CI) 1.16-1.47; P < 0.0001] and non-cardiovascular death (HR 1.47, 95% CI 1.04-2.07; P = 0.031) compared with those with no cancer history. There were no significant associations between cancer history and stroke, venous thromboembolism, or myocardial infarction. The relative efficacy of rivaroxaban vs. warfarin for prevention of stroke/systemic embolism was similar in those with and without a history of cancer (interaction P-value = 0.21). CONCLUSION: In ROCKET AF, a history of cancer was associated with a higher risk of bleeding and non-cardiovascular death, but not ischaemic events. The relative efficacy and safety of rivaroxaban compared with warfarin were not significantly different in patients with and without a history of cancer. The results of this study are exploratory and should be taken in context of the study population, which may not be generalizable to those with advanced malignancy. Further investigation is needed to understand optimal anticoagulation strategies in patients with AF and cancer. Clinical trial registration: ClinicalTrials.gov: NCT00403767.